2014
DOI: 10.1073/pnas.1411233111
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic activation of septal cholinergic neurons suppresses sharp wave ripples and enhances theta oscillations in the hippocampus

Abstract: Theta oscillations in the limbic system depend on the integrity of the medial septum. The different populations of medial septal neurons (cholinergic and GABAergic) are assumed to affect different aspects of theta oscillations. Using optogenetic stimulation of cholinergic neurons in ChAT-Cre mice, we investigated their effects on hippocampal local field potentials in both anesthetized and behaving mice. Cholinergic stimulation completely blocked sharp wave ripples and strongly suppressed the power of both slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
317
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(377 citation statements)
references
References 55 publications
37
317
7
Order By: Relevance
“…Recent studies based on genetic mutations in mice, however, provide strong support for theta rhythm heterogeneity (20,21). Furthermore, recent experiments by Vandecasteel et al demonstrated that optogenetic stimulation of cholinergic MS neurons selectively enhances cholinergic type 2 theta rhythm without affecting noncholinergic type 1 theta rhythm (22). In the present study, we revealed a neural mechanism involved in object exploration distinct from open-field exploration behavior.…”
Section: Optogenetic Modulation Of Septo-hippocampal Gabaergic Fiberssupporting
confidence: 65%
See 1 more Smart Citation
“…Recent studies based on genetic mutations in mice, however, provide strong support for theta rhythm heterogeneity (20,21). Furthermore, recent experiments by Vandecasteel et al demonstrated that optogenetic stimulation of cholinergic MS neurons selectively enhances cholinergic type 2 theta rhythm without affecting noncholinergic type 1 theta rhythm (22). In the present study, we revealed a neural mechanism involved in object exploration distinct from open-field exploration behavior.…”
Section: Optogenetic Modulation Of Septo-hippocampal Gabaergic Fiberssupporting
confidence: 65%
“…Moreover, the MS is also the nodal point for ascending afferent systems involved in the generation of hippocampal theta rhythms, the largest synchronous oscillatory signals in the mammalian brain, which are implicated in diverse brain functions (17,18). Although the heterogeneity of hippocampal theta rhythms has long been under debate (19), recent studies based on genetic mutations in mice and optogenetics provide strong support for theta rhythm heterogeneity (20)(21)(22). However, their exact behavioral correlates are still debated.…”
Section: Ca V 31 T-type Ca2mentioning
confidence: 99%
“…Recent evidence using optogenetic activation of MS-DBB cholinergic neurons suggests that ACh neurons may not significantly take part in theta generation in the hippocampus (Vandecasteele et al, 2014). As for MS-DBB GABAergic neurons, these neurons have unique connectivity to GABAergic interneurons in the hippocampus and strongly fire phase-locked to theta, suggesting that they play an important role in theta generation (Petsche et al, 1962;Freund and Antal, 1988;Stewart and Fox, 1990;Hangya et al, 2009;Bender et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the MS-DBB provides an important input for cell assembly formation in the hippocampus and grid cell organization in the entorhinal cortex (Brandon et al, 2011;Wang et al, 2015). Whereas the traditional model of the septum consists of GABAergic and cholinergic neurons, a third population of glutamatergic neurons expressing Type 2 vesicular glutamate transporters (VGLUT2) was described more recently (Sotty et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%
“…The septalhippocampal circuit, which supports exploratory and attentive behaviors (Vertes and Kocsis 1997), could be one of the competing networks. It has been shown that firing of the medial septal neurons is suppressed around ripples (Dragoi et al 1999;Vandecasteele et al 2014); in turn, activation of the septo-hippocampal pathway suppresses ripple generation (Vandecasteele et al 2014). The medial septum is a major hippocampal afferent and both structures are heavily innervated by NE fibers (Loy et al 1980).…”
Section: Competing Functional Networkmentioning
confidence: 99%